USE OF PEDAGOGICAL QUALIMETRY METHODS (Web of Teachers: Inderscience Research, 2024)
Qualimetry studies the issues of assessing the quality of goods, services, and processes. The main methods of qualimetry in this process are: analysis, synthesis, comparison, and comparison. Based on the quality indicators of the model adopted as a standard, the quality of the object being evaluated is determined, taking into account its characteristics. This article discusses the methods of applying quasimetric methods in the field of pedagogy.